Keterampilan Berpikir sebagai Bagian dari Proses Kognitif Kompleks Siswa - Puspa Dewi; Tsuaibatul Aslamiyah Nasution; Widi Ahmad; Fauziah Nasution (Jurnal Dirosah Islamiyah, 2023)
Thinking is a mental activity that occurs in every human being. As it develops, the problems faced by individuals will become more complex. This triggers humans to have skills in thinking creatively, critically, rationally, and structuredly. This research study uses literature review to obtain data from several reading sources such as books and scientific articles related to students' thinking skills. The way that can be done in helping students become good thinkers is to provide analysis-based questions and direct students to make mind maps. In shaping students with good thinking, the teacher holds a very important position as a guide in compiling ideas and thoughts. Teachers must involve students in every aspect of learning activities in order to create students with creative and critical thinking. Keywords: thinking skills; cognitive; complex cognitive processes.